JEE advanced Physics : chapter wise PYQ analysis - Arora, Ashish (New Delhi GKP, 2022)
This book of PHYSICS GALAXY Solutions of Previous Years of JEE Advanced chapter wise papers is made with detailed comprehensive solutions for each question with elaborated explanation to understand the concept used in application of the questions. For JEE Advanced, this is essential for all aspirants to carefully understand, how to attack on questions in examination hall while reading it for the first time. The solutions given in this book help students in building the attacking ability for JEE Advanced level questions and strengthen out of the box thinking (OTBT) ability.
Keywords: Physics